Digital Business Strategy Maturity, Financial Development and Income Inequality: Empirical Evidence from a Panel of 149 Countries - Lacombe, Isabelle; Amari, Mouna; Mouakhar, Khaireddine; Jarboui, Anis (Management international / International Management / Gestiòn Internacional, 2022)
The purpose of this paper is to study the impact of Digital Business Strategy (DBS) on income inequality. This study investigates how DBS complements financial development in order to influence income inequality in a large panel of 149 countries relying on the GMM estimations for the period 2012 to 2016. Results show that digitalisation helps reduce inequality across countries that belong to the high and the medium DBS maturity levels. This paper highlights the importance of building a mature DBS both for enhancing the positive effects of technology innovation and for promoting financial development as a solution to income inequality.